Legal Framework and Effectiveness of Bank Resolution by the Indonesia Deposit Insurance Corporation - Diana R.W. Napitupulu; Mohammad Belayet Hossain; Bahrullah Akbar (Unissula, 2025)
Bank failures pose serious systemic risks to financial stability and public confidence. In Indonesia, the Deposit Insurance Corporation plays a crucial role in resolving troubled banks to maintain financial system stability and protect customers. This study aims to analyze the legal framework for bank resolution, specifically the Deposit Insurance Corporation authority, responsibilities, and mechanisms for dealing with troubled banks, and the extent to which Law Number 24 of 2004 and Law Number 9 of 2016 provide legal certainty and support systemic stability. The research method uses a normative legal approach, examining relevant laws and regulations, including early intervention mechanisms, resolution planning, and resolution strategies such as purchase and assumption, bridge banking, and liquidation. The interaction between Deposit Insurance Corporation, Bank of Indonesia, and the Financial Services Authority is also examined to understand inter-authority coordination in crisis scenarios. The findings indicate that the current legal framework is flexible enough to handle troubled banks, but still faces challenges in coordination, transparency, and legal certainty. In conclusion, Deposit Insurance Corporation has a central role, but the effectiveness of resolution depends on clear mechanisms, good coordination, and a strengthened legal framework to maintain the credibility and stability of the Indonesian financial system.